USP20 is a predictor of poor prognosis in colorectal cancer and associated with lymph node metastasis, immune infiltration and chemotherapy resistance - Jin, RuiRi; Luo, ZhiPeng; Jun-Li,; Tao, Qing; Wang, Peng; Cai, XueSheng; Jiang, LongZhou; Zeng, ChunYan; Chen, YouXiang (Frontiers in Oncology, 2023)
Background Colorectal cancer (CRC) is a highly prevalent malignancy with a poor prognosis. USP20 can support progression of variety of tumors. USP20 was shown to promote breast tumor metastasis, and proliferation of oral squamous carcinoma cells. However, the role of USP20 in CRC remains unclear. Methods We used bioinformatics to analyze the expression and prognosis of USP20 in pan-cancer and explore the relationship between USP20 expression and immune infiltration, immune checkpoints, and chemotherapy resistance in CRC. The differential expression and prognostic role of USP20 in CRC was validated by qRT-PCR and immunohistochemistry. Cox univariate and multivariate analyses were performed to assess risk factors for poor prognosis of CRC, and new prognostic prediction models were constructed and evaluated by decision curve analysis (ROC) and receiver operating characteristic (DCA). USP20 was overexpressed in CRC cell lines to explore the effect of USP20 on the functionalities of CRC cells. Enrichment analyses were used to explore the possible mechanism of USP20 in CRC. Results The expression of USP20 was lower in CRC tissues than adjacent normal tissues. Compared with low USP20 expression patients, CRC patients with high USP20 expression level had shorter OS. Correlation analysis showed that USP20 expression was associated with lymph node metastasis. Cox regression analysis revealed USP20 as an independent risk factor for poor prognosis in CRC patients. ROC and DCA analyses showed that the performance of the newly constructed prediction model was better than the traditional TNM model. Immune infiltration analysis shown that USP20 expression is closely associated with T cell infiltration in CRC. A co-expression analysis showed that USP20 expression was positively correlated with several immune checkpoint genes including ADORA2A, CD160, CD27 and TNFRSF25 genes and positively associated with multiple multi-drug resistance genes such as MRP1, MRP3, and MRP5 genes. USP20 expression positively correlated with the sensitivity of cells to multiple anticancer drugs. Overexpression of USP20 enhanced the migration and invasive ability of CRC cells. Enrichment pathway analyses showed the USP20 may play a role via the Notch pathway, Hedgehog pathway and beta-catenin pathway. Conclusion USP20 is downregulated in CRC and associated with prognosis in CRC. USP20 enhances CRC cells metastasis and is associated with immune infiltration, immune checkpoints, and chemotherapy resistance.